2020
DOI: 10.3847/1538-4365/ab665a
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic Signatures of Reverberation Mapping of Close Binaries of Supermassive Black Holes in Active Galactic Nuclei. II. Atlas of Two-dimensional Transfer Functions

Abstract: Most large galaxies harbor supermassive black holes (SMBHs) in their centers, and galaxies merge. Consequently, binary SMBHs should be common in galactic nuclei. However, close binaries of SMBH (CB-SMBHs) with sub-parsec separation cannot be imaged directly using current facilities. Some indirect signatures, such as periodic signals in light curves and double peaks in emission-line profile, have been used to find CB-SMBH candidates, but ambiguities still exist and no definitive conclusions can be made. We have… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 77 publications
0
22
0
Order By: Relevance
“…Previous studies have focused on the 2DTFs of BLR clouds and BEL profiles emitted from two separate BLRs surrounding each of the two BHs at larger separations, i.e., R BLR /a BBH < 1 (e.g., Shen & Loeb 2010;Wang et al 2018;Songsheng et al 2020;Kovačević et al 2020). The configuration of a BLR-BBH system, especially for disklike BLRs, can be structured by a series of parameter combinations, such as opening angles and inclination angles of the BLR, BLR size or bolometric luminosity of the two BHs, the kinematics of the BLR clouds, i.e., inflow, outflow, or Keplerian orbit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have focused on the 2DTFs of BLR clouds and BEL profiles emitted from two separate BLRs surrounding each of the two BHs at larger separations, i.e., R BLR /a BBH < 1 (e.g., Shen & Loeb 2010;Wang et al 2018;Songsheng et al 2020;Kovačević et al 2020). The configuration of a BLR-BBH system, especially for disklike BLRs, can be structured by a series of parameter combinations, such as opening angles and inclination angles of the BLR, BLR size or bolometric luminosity of the two BHs, the kinematics of the BLR clouds, i.e., inflow, outflow, or Keplerian orbit.…”
Section: Discussionmentioning
confidence: 99%
“…In the above calculations and analyses, we assume that all BLR clouds distribute around a uniform BLR middle plane with an initial opening angle of 30 • , however, the circumbinary BLR might consist of two components, which come from the two separate BLRs associate with each of the two BHs when they are on a much larger separation during the BBH evolution process (e.g., Wang et al 2018;Songsheng et al 2020;Kovačević et al 2020).…”
Section: Bel Profile Variation For a Misaligned Blr With Different Co...mentioning
confidence: 99%
“…AGNs are monitored with the Hβ Asymmetry (MAHA), which is a long-term campaign searching for CB-SMBHs (Du et al 2018). We hope to see signals of CB-SMBHs from their 2D transfer functions (Wang et al 2018;Kovačević et al 2020a;Songsheng et al 2020, see a recent review of Wang & Li 2020) as well as signals revealed by GRAVITY/VLTI (Songsheng et al 2019;Kovačevič et al 2020b). CL-AGNs could be the best candidates of CB-SMBHs.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…There have been a number of studies to investigate the detailed variation pattern of BELs from subparsec BBH systems (e.g., Shen & Loeb 2010;Wang et al 2018;Songsheng et al 2020;Kovačević et al 2020); these mainly focused on the line profiles and their variations for those BBH systems with two separate BLRs associated with each of the two BH components. Recently, Wang et al (2018) and Songsheng et al (2020) have shown the distinctive structures of BBH systems in the two-dimensional transfer functions (2DTFs) and demonstrated the possibility of using the RM technique to reveal BBH systems (see also Kovačević et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…There have been a number of studies to investigate the detailed variation pattern of BELs from subparsec BBH systems (e.g., Shen & Loeb 2010;Wang et al 2018;Songsheng et al 2020;Kovačević et al 2020); these mainly focused on the line profiles and their variations for those BBH systems with two separate BLRs associated with each of the two BH components. Recently, Wang et al (2018) and Songsheng et al (2020) have shown the distinctive structures of BBH systems in the two-dimensional transfer functions (2DTFs) and demonstrated the possibility of using the RM technique to reveal BBH systems (see also Kovačević et al 2020). We note here that the BBH candidates suggested by periodicity continuum variations (Graham et al 2015b;Charisi et al 2016) may have BLRs with sizes substantially larger than the inferred BBH semimajor axes (e.g., Song et al 2020Song et al , 2021, i.e., circumbinary BLRs, which are in a different category from those cases with two separate BLRs in the above-mentioned studies.…”
Section: Introductionmentioning
confidence: 99%